PROCESSO ELEITORAL COMO EXERCÍCIO DA CIDADANIA - Pimenta, Dagmar Cambauva Baptista; Almeida, Liliane Miranda; Rocha, Marcia Cristina de Brito; Cardoso, Rosemeire Doná; Rocco, Anderson; Pina, Regina Maria (Revista Ciências Jurídicas e Sociais - UNG-Ser, 2014)
... ver texto na íntegra.